Pemodelan Propagasi Gelombang pada Linear Shallow Water Equations Menggunakan Metode Spectral - Setyo Nugroho; Mohamad Riyadi (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2015)
ABSTRACTÂ In this paper , the propagation of waves with an initial condition on the foundation are varied( varying bottom ) simulated by the model Linear Shallow Water Equations ( LSWE ) 1D . 1D LSWE solution with an initial condition was approached with numerical solutions , which use spectral methods . To reduce waves so as not to repeat back to the spatial domain need to be defined damping zone. The simulation results showed that the more superficial level it will increase the amplitude of the wave .Â Keywords : Wave Propagation , LSWE ID , Varying Bottom , MetodeSspectral , Damping Zone